Qur’anic Tahfiz and the Development of Student Discipline in Islamic Education - Bukhoril Hafiz; Khairuddin Lubis (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
This study examines the contribution of the Qur’anic tahfiz program to the formation of students’ discipline character at MTs Al-Washliyah Gedung Johor. The study employed a qualitative descriptive approach through field research. Data were collected through observation, semi-structured interviews, and documentation involving the madrasah principal, tahfiz teachers, and participating students. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing and verification. The findings indicate that the Qur’anic tahfiz program contributes to students’ discipline character through continuous habituation, teacher supervision, role-modeling, and the internalization of Islamic values. Activities including talaqqi, tikrar, muraja’ah, tasmi’, and memorization targets train students to manage time, fulfill responsibilities, comply with regulations, maintain consistency, and develop self-control. The study also reveals that the Islamic culture of the madrasah and family support strengthen the sustainability of students’ disciplinary habits. Therefore, the Qur’anic tahfiz program functions not merely as a memorization-oriented learning activity but also as a Qur’an-based character education model that integrates religious learning with the development of disciplined, responsible, consistent, and morally grounded students.